Resonant evanescent excitation of OAM modes in a high-contrast circular step-index fiber - Hammer, Manfred; Ebers, Lena; Förstner, Jens (Complex Light and Optical Forces XVI)
Resonant evanescent coupling can be utilized to selectively excite orbital angular momentum (OAM) modes of high angular order supported by a thin circular dielectric rod. Our 2.5-D hybrid-analytical coupled mode model combines the vectorial fields associated with the fundamental TE- and TM-modes of a standard silicon photonics slab waveguide, propagating at oblique angles with respect to the rod axis, and the hybrid modes supported by the rod. One observes an efficient resonant interaction in cases where the common axial wavenumber of the waves in the slab matches the propagation constant of one or more modes of the rod. For certain modes of high angular order, the incident wave is able to transfer its directionality to the field in the fiber, exciting effectively only one of a pair of degenerate OAM modes
Keywords: tet_topic_waveguide

Semi-guided waves in integrated optical waveguide structures - Ebers, Lena
In dieser Arbeit wird die elektromagnetische Wellenausbreitung in integrierten optischen Wellenleitern mit Hilfe von halb analytischen und numerischen Simulationsmethoden untersucht. Im ersten Teil werden 2-D Si/SiO2-Wellenleiterkonfigurationen mit hohem Brechungsindexkontrast betrachtet. Die Strukturen werden mit halb geführten Wellen unter schrägen Ausbreitungswinkeln angeregt. Dadurch kann die Leistungsübertragung zu bestimmten ausgehenden Moden unterdrückt werden, wodurch vollständig verlustfreie Systeme entstehen. Zusätzlich dient die Anregung mit einem seitlich begrenzten, einfallenden Wellenbündel aus halb geführten Wellen dazu, praktisch relevantere 3-D Konfigurationen zu realisieren. Darüber hinaus wird eine schrittweise Winkelspektrum-Methode vorgestellt, die es ermöglicht, in Kombination mit voll vektoriellen 2-D Finite-Elemente-Lösungen für Teilprobleme mit geringerer Komplexität, die Wellenausbreitung in planaren, linsenförmigen Wellenleitern numerisch in drei Raumrichtungen zu berechnen. Im zweiten Teil dieser Arbeit wird die Ausbreitung in Wellenleiterstrukturen aus Lithiumniobat untersucht, welche für quantenoptische Effekte genutzt werden. Zur Detektion einzelner Photonen werden supraleitende Nanodrähte auf eindiffundierten Lithiumniobat Wellenleitern mit zusätzlicher Taperschicht aus Silizium betrachtet. Um die Wellenausbreitung in diesen 3-D Wellenleitern zu beschreiben, wird eine einseitig gerichtete Finite-Elemente „Modal Matching“ Methode eingeführt. Abschließend werden Rippenwellenleiter aus Lithiumniobat analysiert, die auf Siliziumdioxid Plattformen aufgebracht sind. Der Schwerpunkt liegt hier auf dem nichtlinearen „Parametric Down-Conversion“ Prozess, der für die Erzeugung verschränkter Photonen verwendet wird.
Keywords: tet_topic_waveguide

Flexible source of correlated photons based on LNOI rib waveguides - Ebers, Lena; Ferreri, Alessandro; Hammer, Manfred; Albert, Maximilian; Meier, Cedrik; Förstner, Jens; Sharapova, Polina R. (Journal of Physics: Photonics)
Lithium niobate on insulator (LNOI) has a great potential for photonic integrated circuits, providing substantial versatility in design of various integrated components. To properly use these components in the implementation of different quantum protocols, photons with different properties are required. In this paper, we theoretically demonstrate a flexible source of correlated photons built on the LNOI waveguide of a special geometry. This source is based on the parametric down-conversion (PDC) process, in which the signal and idler photons are generated at the telecom wavelength and have different spatial profiles and polarizations, but the same group velocities. Distinguishability in polarizations and spatial profiles facilitates the routing and manipulating individual photons, while the equality of their group velocities leads to the absence of temporal walk-off between photons. We show how the spectral properties of the generated photons and the number of their frequency modes can be controlled depending on the pump characteristics and the waveguide length. Finally, we discuss special regimes, in which narrowband light with strong frequency correlations and polarization-entangled Bell states are generated at the telecom wavelength.
Keywords: tet_topic_waveguide

Resonant evanescent excitation of guided waves with high-order optical angular momentum - Hammer, Manfred; Ebers, Lena; Förstner, Jens (Journal of the Optical Society of America B)
Gaussian-beam-like bundles of semi-guided waves propagating in a dielectric slab can excite modes with high-order optical angular momentum supported by a circular fiber. We consider a multimode step-index fiber with a high-index coating, where the waves in the slab are evanescently coupled to the modes of the fiber. Conditions for effective resonant interaction are identified. Based on a hybrid analytical–numerical coupled mode model, our simulations predict that substantial fractions of the input power can be focused into waves with specific orbital angular momentum, of excellent purity, with a clear distinction between degenerate modes with opposite vorticity.
Keywords: tet_topic_waveguides

Configurable lossless broadband beam splitters for semi-guided waves in integrated silicon photonics - Hammer, Manfred; Ebers, Lena; Förstner, Jens (OSA Continuum)
We show that narrow trenches in a high-contrast silicon-photonics slab can act as lossless power dividers for semi-guided waves. Reflectance and transmittance can be easily configured by selecting the trench width. At sufficiently high angles of incidence, the devices are lossless, apart from material attenuation and scattering due to surface roughness. We numerically simulate a series of devices within the full 0-to-1-range of splitting ratios, for semi-guided plane wave incidence as well as for excitation by focused Gaussian wave bundles. Straightforward cascading of the trenches leads to concepts for 1×M-power dividers and a polarization beam splitter.
Keywords: tet_topic_waveguide

Integrated superconducting nanowire single-photon detectors on titanium in-diffused lithium niobate waveguides - Höpker, Jan Philipp; Verma, Varun B; Protte, Maximilian; Ricken, Raimund; Quiring, Viktor; Eigner, Christof; Ebers, Lena; Hammer, Manfred; Förstner, Jens; Silberhorn, Christine; Mirin, Richard P; Woo Nam, Sae; et al. (Journal of Physics: Photonics)
We demonstrate the integration of amorphous tungsten silicide superconducting nanowire single-photon detectors on titanium in-diffused lithium niobate waveguides. We show proof-of-principle detection of evanescently coupled photons of 1550 nm wavelength using bidirectional waveguide coupling for two orthogonal polarization directions. We investigate the internal detection efficiency as well as detector absorption using coupling-independent characterization measurements. Furthermore, we describe strategies to improve the yield and efficiency of these devices.

Hybrid coupled mode modelling of the evanescent excitation of a dielectric tube by semi-guided waves at oblique angles - Hammer, Manfred; Ebers, Lena; Förstner, Jens (Optical and Quantum Electronics)
A dielectric step-index optical fiber with tube-like profile is considered, being positioned with a small gap on top of a dielectric slab waveguide. We propose a 2.5-D hybrid analytical/numerical coupled mode model for the evanescent excitation of the tube through semi-guided waves propagating in the slab at oblique angles. The model combines the directional polarized modes supported by the slab with analytic solutions for the TE-, TM-, and orbital-angular-momentum (OAM) modes of the tube-shaped fiber. Implementational details of the scheme are discussed, complemented by finite-element simulations for verification purposes. Our results include configurations with resonant in-fiber excitation of OAM modes with large orbital angular momentum and strong field enhancement.
Keywords: tet_topic_waveguides

Light diffraction in slab waveguide lenses simulated with the stepwise angular spectrum method - Ebers, Lena; Hammer, Manfred; Förstner, Jens (Optics Express)
A stepwise angular spectrum method (SASM) for curved interfaces is presented to calculate the wave propagation in planar lens-like integrated optical structures based on photonic slab waveguides. The method is derived and illustrated for an effective 2D setup first and then for 3D slab waveguide lenses. We employ slab waveguides of different thicknesses connected by curved surfaces to realize a lens-like structure. To simulate the wave propagation in 3D including reflection and scattering losses, the stepwise angular spectrum method is combined with full vectorial finite element computations for subproblems with lower complexity. Our SASM results show excellent agreement with rigorous numerical simulations of the full structures with a substantially lower computational effort and can be utilized for the simulation-based design and optimization of complex and large scale setups.
Keywords: tet_topic_waveguides

Towards Semiconductor-Superconductor-Crystal Hybrid Integration for Quantum Photonics - Protte, Maximilian; Ebers, Lena; Hammer, Manfred; Höpker, Jan Philipp; Albert, Maximilian; Quiring, Viktor; Meier, Cedrik; Förstner, Jens; Silberhorn, Christine; Bartley, Tim (OSA Quantum 2.0 Conference)
We fabricate silicon tapers to increase the mode overlap of superconducting detectors on Ti:LiNbO3 waveguides. Mode images show a reduction in mode size from 6 µm to 2 µm FWHM, agreeing with beam propagation simulations.
Keywords: tet_topic_waveguide

Oblique quasi-lossless excitation of a thin silicon slab waveguide: a guided-wave variant of an anti-reflection coating - Hammer, Manfred; Ebers, Lena; Förstner, Jens (Journal of the Optical Society of America B)
Keywords: tet_topic_waveguides

Coupled microstrip-cavities under oblique incidence of semi-guided waves: a lossless integrated optical add-drop filter - Ebers, Lena; Hammer, Manfred; Berkemeier, Manuel B.; Menzel, Alexander; Förstner, Jens (OSA Continuum)
We investigate optical microresonators consisting of either one or two coupled rectangular strips between upper and lower slab waveguides. The cavities are evanescently excited under oblique angles by thin-film guided, in-plane unguided waves supported by one of the slab waveguides. Beyond a specific incidence angle, losses are fully suppressed. The interaction between the guided mode of the cavity-strip and the incoming slab modes leads to resonant behavior for specific incidence angles and gaps. For a single cavity, at resonance, the input power is equally split among each of the four output ports, while for two cavities an add-drop filter can be realized that, at resonance, routes the incoming power completely to the forward drop waveguide via the cavity. For both applications, the strength of the interaction is controlled by the gaps between cavities and waveguides.
Keywords: tet_topic_waveguides

Optical transition between two optical waveguides layer and method for transmitting light - Hammer, Manfred; Förstner, Jens; Ebers, Lena
Die Erfindung betrifft einen optischen Übergang zwischen zwei optischen Schichtwellenleitern. Dazu ist eine Anordnung vorgesehen aus einem ersten optischen Schichtwellenleiter (2) und einem zweiten optischen Schichtwellenleiter (3), wobei der erste optische Schichtwellenleiter (2) und der zweite optische Schichtwellenleiter (3) voneinander verschiedene über ihre jeweilige Länge konstante Dicken (d, r) aufweisen, der erste optische Schichtwellenleiter (2) mit dem zweiten optischen Schichtwellenleiter (3) mittels einer optischen Schichtwellenleiterstruktur (4) verbunden ist, die über ihre gesamte Länge (w) eine Dicke (h) aufweist, die zwischen der Dicke (d) des ersten optischen Schichtwellenleiters (2) und der Dicke (r) des zweiten optischen Schichtwellenleiters (3) liegt. Erfindungsgemäß ist die Dicke (h) der optischen Schichtwellenleiterstruktur (4) über die gesamte Länge (w) der optischen Schichtwellenleiterstruktur (4) konstant. Damit wird eine Möglichkeit für einen effizienten und mit geringen Verlusten behafteten Übergang zwischen zwei optischen Schichtwellenleitern mit unterschiedlicher Dicke bereitgestellt.
Keywords: tet_topic_waveguides

Oblique evanescent excitation of a dielectric strip: A model resonator with an open optical cavity of unlimited Q - Hammer, Manfred; Ebers, Lena; Förstner, Jens (Optics Express)
A rectangular dielectric strip at some distance above an optical slab waveguide is being considered, for evanescent excitation of the strip through the semi-guided waves supported by the slab, at specific oblique angles. The 2.5-D configuration shows resonant transmission properties with respect to variations of the angle of incidence, or of the excitation frequency, respectively. The strength of the interaction can be controlled by the gap between strip and slab. For increasing distance, our simulations predict resonant states with unit extremal reflectance of an angular or spectral width that tends to zero, i.e. resonances with a Q-factor that tends to infinity, while the resonance position approaches the level of the guided mode of the strip. This exceptionally simple system realizes what might be termed a “bound state coupled to the continuum”.
Keywords: tet_topic_waveguides

Oblique incidence of semi-guided planar waves on slab waveguide steps: effects of rounded edges - Ebers, Lena; Hammer, Manfred; Förstner, Jens (Optics Express)
Oblique propagation of semi-guided waves across slab waveguide structures with bent corners is investigated. A critical angle can be defined beyond which all radiation losses are suppressed. Additionally an increase of the curvature radius of the bends also leads to low-loss configurations for incidence angles below that critical angle. A combination of two bent corner systems represents a step-like structure, behaving like a Fabry-Perot interferometer, with two partial reflectors separated by the vertical height between the horizontal slabs. We numerically analyse typical high-index-contrast Si/SiO2 structures for their reflectance and transmittance properties. When increasing the curvature radius the resonant effect becomes less relevant such that full transmittance is reached with less critical conditions on the vertical distance or the incidence angle. For practical interest 3-D problems are considered, where the structures are excited by the fundamental mode of a wide, shallow rib waveguide. High transmittance levels can be observed also for these 3-D configurations depending on the width of the rib.
Keywords: tet_topic_waveguide

Oblique Semi-Guided Waves: 2-D Integrated Photonics with Negative Effective Permittivity - Hammer, Manfred; Ebers, Lena; Hildebrandt, Andre; Alhaddad, Samer; Förstner, Jens (2018 IEEE 17th International Conference on Mathematical Methods in Electromagnetic Theory (MMET))
Semi-guided waves confined in dielectric slab waveguides are being considered for oblique angles of propagation. If the waves encounter a linear discontinuity of (mostly) arbitrary shape and extension, a variant of Snell's law applies, separately for each pair of incoming and outgoing modes. Depending on the effective indices involved, and on the angle of incidence, power transfer to specific outgoing waves can be allowed or forbidden. In particular, critical angles of incidence can be identified, beyond which any power transfer to non-guided waves is forbidden, i.e. all radiative losses are suppressed. In that case the input power is carried away from the discontinuity exclusively by reflected semi-guided waves in the input slab, or by semi-guided waves that are transmitted into other outgoing slab waveguides. Vectorial equations on a 2-D cross sectional domain apply. These are formally identical to the equations that govern the eigenmodes of 3-D channel waveguides. Here, however, these need to be solved not as an eigenvalue problem, but as an inhomogeneous problem with a right-hand-side that is given by the incoming semi-guided wave, and subject to transparent boundary conditions. The equations resemble a standard 2-D Helmholtz problem, with an effective permittivity in place of the actual relative permittivity. Depending on the properties of the incoming wave, including the angle of incidence, this effective permittivity can become locally negative, causing the suppression of propagating outgoing waves. A series of high-contrast example configurations are discussed, where these effects lead to - in some respects - quite surprising transmission characteristics.
Keywords: tet_topic_waveguides

Spiral modes supported by circular dielectric tubes and tube segments - Ebers, Lena; Hammer, Manfred; Förstner, Jens (Optical and Quantum Electronics)
The modal properties of curved dielectric slab waveguides are investigated. We consider quasi-confined, attenuated modes that propagate at oblique angles with respect to the axis through the center of curvature. Our analytical model describes the transition from scalar 2-D TE/TM bend modes to lossless spiral waves at near-axis propagation angles, with a continuum of vectorial attenuated spiral modes in between. Modal solutions are characterized in terms of directional wavenumbers and attenuation constants. Examples for vectorial mode profiles illustrate the effects of oblique wave propagation along the curved slab segments. For the regime of lossless spiral waves, the relation with the guided modes of corresponding dielectric tubes is demonstrated.
Keywords: tet_topic_waveguide